HUBUNGAN IDENTITAS NASIONAL DENGAN POLA AKULTURASI REMAJA ETNIS TIONGHOA DI JAKARTA - Ninawati Ninawati; Kurnia Setiawan; Meiske Yunithree Suparman (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Tarumanagara, 2022)
Ethnic Chinese are one of the minority groups in Indonesia who often receive discriminatory treatment. However, despite receiving continuous discrimination, the Chinese still